Pengaruh Model Think Talk Write Berbantuan Kartu Kalimat Terhadap Kemampuan Menulis Teks Naraasi Siswa Kelas V SDN 33 Kota Bima Tahun Ajaran 2020/2021 - Sumiarti, Titi; Zain, Moh. Irawan; Setiawan, Heri (Pendagogia: Jurnal Pendidikan Dasar, 2022)
This study aimed to determine the effect of the sentence-card assited Think Talk Write model of the students’ writing skill for the 5th grade of the SDN 33 Bima City academic year 2020/2021. This study was used sentence-card assited Think Talk Write model. The population and sample in this study were all students of the 5th grade of the SDN 33 Bima City academic year 2020/2021 which was consists of V A and V B grade with total 29 students. The sample in this study were collected using Sampling Jenuh technique it was by making all population as the sample. The data in this study were collected by students’ writing skill test result for the feasibility of the applief learning model. The testing requirement analysis was used normalityband homogenity test. The students’ writing data were analyzed using Indepent Sample T-test that is score Tcount > Ttable is 2.218>2.045 and the students’ avarage score of the experiment class is 81.43>73.66 of the control class. This shows that nil hypothesis (H₀) is rejected and research hypothesis (H₁) is accepted then it can be concluded that there is the effect of the sentence card-assisted Think Talk Write model of the students’ narration writing skill of the 5th grade of the SDN 33 Bima City academic year 2022/2021.